AGENSI HAKIM PENGADILAN AGAMA BANGKALAN DALAM PEMENUHAN HAK ISTRI PASCA CERAI - Galuh Widitya Qomaro (IAIN Syekh Nurjati Cirebon, 2021)
The Bangkalan Religious Court report in 2019 stated that there were 1051 cases for judicial divorce, while 694 cases for talaq divorce. Based on the increasing number of divorce cases every year, the Religious Courts are required to be able to resolve Islamic family law issues in accordance with the sense of justice for the litigants. This research is a text-based study through reading court decisions from a gender perspective. This study aims to: (1) identify the implications of a legal divorce for the wife's rights after divorce; (2) Identifying the suitability of legal products in the Bangkalan Religious Court regarding the rights of wives after divorce with gender justice. This type of research is qualitative research with field research through data search in the Bangkalan Religious Court. The nature of the research is descriptive-analytic using a gender approach with indicators of maslahah, including: not based on stereotypes, does not result in marginalization, does not result in gender-based violence, is not based on subordination. The results showed that the legal product in the Bangkalan Religious Court regarding the rights of the wife after divorce was in accordance with the principle of gender justice because the judge sentenced the ex-husband to pay for the mut'ah or iddah income for the plaintiff based on the ex-officio rights of the judge and based on the request of the ex-wife on the petitum lawsuit and at the conference lawsuit.